(untitled) (International Journal of Information Technology and Computer Engineering, 2022)
One of the most common diseases which is seen in women and men is a heart disease which has cases throughout the world. The most common type of heart disease is heart arrhythmias, Cardiomyopathy, valvular heart disease and heart failure. Machine learning techniques are performing a vital role in detecting heart disease by analyzing the features like chest pain, resting blood pressure, maximum heart rate, numberof major vessels that can predict whether the person has heart disease or not. The designedmethod in this paper is to build three differentmodels where one model is trained and testedon the whole dataset and remaining two models are trained and tested on male and female patient’s data and the accuracy of the three models are compared.